Pengaruh Pengendalian Internal, Kesesuaian Kompensasi, dan Moralitas Individu terhadap Kecenderungan Kecurangan Akuntansi pada Perbankan di Kota Bukittinggi - Herfen, Rafi Prima; Nelvirita, Nelvirita (Universitas Negeri Padang, 2025)
This research aims at identifying factors that cause accounting fraud using the fraud triangle theory. Previous studies used attribution theory and the fraud diamond theory, whereas this study implements agency theory and the fraud triangle theory. Furthermore, previous studies considered only two variables: internal control and individual morality. This research introduces a third variable, which is compensation suitability. This analysis utilizes a quantitative approach. The reference is derived from primary data, gathered directly from respondents' answers to the questionnaires. The study’s population consisted of employees or workers who worked in the sectors of accounting and finance selected from banks in Bukittinggi City. The study shows that internal control exerts a significant negative impact, suggesting enhanced internal controls can significantly decrease fraudulent activities. However, compensation suitability and individual morality do not significantly affect negative effect on accounting fraud.